Case Report: Bacterial meningitis due to cerebrospinal fluid leakage following unilateral biportal endoscopic spinal surgery: a cautionary tale - Wang, Haoyu; Wang, Yunhui; Jiang, Zhensong; Zhang, Wen (Frontiers in Surgery, 2024)
Unilateral biportal endoscopic spinal surgery (UBE) is a rapidly growing surgical method and has attracted much interest recently. The most common complication of this technique is cerebrospinal fluid (CSF) leakage due to intraoperative dural tears. There have been no reports of bacterial meningitis due to dural tears in UBE surgery and its treatment and prevention. We reported a 47 year-old man with CSF due to an intraoperative dural tear. A drainage tube was routinely placed and removed on the fourth day after surgery, resulting in fever and headache on the fifith postoperative day. Blood and CSF cultures showed Klebsiella pneumoniae infection, and with lumbar drainage and appropriate antibiotics based on sensitivity tests, the patient's fever and headache were effectively relieved. This case report suggests the importance of prolonged drainage tube placement, adequate drainage, careful intraoperative separation to avoid dural tears, and effective sensitive antibiotic therapy.